Crack Protective Layered Architecture of Lead-Free Piezoelectric Energy Harvester in Bistable Configuration - Rubes, Ondrej; Machu, Zdenek; Sevecek, Oldrich; Hadas, Zdenek (Sensors (Basel, Switzerland), 2020)
Kinetic piezoelectric energy harvesters are used to power up ultra-low power devices without batteries as an alternative and eco-friendly source of energy. This paper deals with a novel design of a lead-free multilayer energy harvester based on BaTiO3 ceramics. This material is very brittle and might be cracked in small amplitudes of oscillations. However, the main aim of our development is the design of a crack protective layered architecture that protects an energy harvesting device in very high amplitudes of oscillations. This architecture is described and optimized for chosen geometry and the resulted one degree of freedom coupled electromechanical model is derived. This model could be used in bistable configuration and the model is extended about the nonlinear stiffness produced by auxiliary magnets. The complex bistable vibration energy harvester is simulated to predict operation in a wide range of frequency excitation. It should demonstrate typical operation of designed beam and a stress intensity factor was calculated for layers. The whole system, without presence of cracks, was simulated with an excitation acceleration of amplitude up to 1g. The maximal obtained power was around 2 mW at the frequency around 40 Hz with a maximal tip displacement 7.5 mm. The maximal operating amplitude of this novel design was calculated around 10 mm which is 10-times higher than without protective layers.
Keywords: bistable energy harvester; bimorph; nonlinear resonators; lead free ceramic; energy harvesting; piezoelectrics